European welfare state constitutions after the financial crisis - 1988-; Poulou, Anastasia 1960- (Oxford Oxford University Press, 2020)
Hit by the European financial and economic crisis in 2008, several Member States of the European Monetary Union (EMU) were unable to refinance their public debt through the financial markets. As a result, they asked for financial assistance from international institutions and European financial assistance mechanisms. That assistance often came at a high price for citizens, cuts in pensions and social assistance, and controversial reforms in public healthcare. These far-reaching reforms were, in many cases, experienced as violations of people's human rights. National constitutional courts, the Court of Justice of the EU, and the European Court of Human Rights issued a series of rulings on the conformity of the reforms in social protection initiated during the Eurozone crisis. This book offers a holistic analysis of the specific reforms in social protection introduced during the European financial crisis and their implications for constitutional law. Focusing on the social reforms of nine European countries that were greatly affected by the financial crisis, the volume seeks to address the legacy of the financial crisis on the application of constitutional law and the welfare state. The book will act as a helpful tool to legal academics interested in the challenges of constitutional and social law initiated by financial assistance conditionality, to advocates in quest of sound legal bases for the protection of individuals affected by social security reforms, and to national and international judges who are confronted with cases that question the legality and legitimacy of the crisis-related reforms.
Introduction Ulrich Becker -- Human rights obligations of European financial assistance mechanisms Anastasia Poulou -- The transition from welfare to workfare in times of crises : a double-based reform of the Hungarian welfare state József Hajdú -- The Latvian response to its first economic crises under a free market economy Kristīne Dupate -- Upholding the welfare state during the financial crisis : the pivotal role of the Constitutional Court of Romania Elena-Luminiţa Dima -- Salus rei publicae suprema lex esto? : welfare state reforms before the Greek courts Maria Bakavou -- The financial crisis as a turning point for constitutional rights jurisprudence : an assessment of the absence of social rights protection in the Irish constitution Elaine Dewhurst -- Legal changes and constitutional adjudication in Portuguese social law in consequence of the European financial crisis José Carlos Vieira de Andrade, João Carlos Loureiro, and Suzana Tavares da Silva -- A 'bail-in' of social rights? : the Cypriot experience of the financial crisis Constantinos Kombos and Athena Herodotou -- The outcome of the financial crisis in Italy : a sea change for the doctrine of social rights Matteo De Nes and Andrea Pin -- The predominance of a 'strong' economy over a 'weak' social constitution : the legacy of the financial crisis in Spain Juan Antonio Maldonado Molina and Juan Romero Coronado -- Conclusions from a comparative perspective Ulrich Becker.
Includes bibliographical references and index.
Keywords: Financial crisis; Constitutional law. -- EU/EC Law; Public welfare -- Electronic books -- Europe; Welfare state -- Aspect social; Constitutional law; Global Financial Crisis, 2008-2009 -- Social aspects; Welafare state -- Global Financial crisis -- Europe; Financial crisis. -- Public welfare; Europe; Constitutional history. -- Global Financial crisis; European; Constitutional history -- 21st century. -- European Union countries; Social aspects; Welfare state; 21e siècle. -- Pays de l'Union européenne; Histoire -- 21e siècle. -- Pays de l'Union européenne; Public welfare -- Law and legislation; Welfare state -- Constitutional law -- History -- 21st century. -- European Union countries; Welfare state -- Public welfare -- Law and legislation -- History -- 21st century. -- European Union countries